Assembly of new histones into nucleosomes and their distribution in replicating chromatin. - Russev, G (1982)
We studied the assembly of new histones into nucleosomes and their distribution in replicating chromatin in growing P815 mouse cells. New histones and new DNA were density-labeled with 13C, 15N, 2H-substituted amino acids together with [3H]arginine or with 5-iododeoxyuridine and [3H]thymidine, respectively, for 1 hr (approximately 20% of S phase). Mono- di-, tri-, tetra- and larger oligonucleosomes were isolated by sucrose gradient centrifugation of micrococcal nuclease-digested chromatin, and their density distribution was analyzed, without fixation, in metrizamide/triethanolamine density gradients [Russev, G. and Tsanev, R. (1976) Nucleic Acids Res. 3, 697-707] in which mono- and oligonucleosomes containing dense amino acids or 5-iododeoxyuridine separate from the corresponding normal nucleosomes. Under these conditions, approximately 74% of the new histones are found in nucleosomes on newly replicated DNA, and the remainder are on unreplicated DNA. The majority of new histones form entirely new nucleosomes; a minor fraction may form hybrid nucleosomes that also contain preexisting histones. New nucleosomes are distributed to both new daughter DNA molecules with approximately equal probability, and our evidence suggests, but does not prove, that they are distributed in a random manner along new DNA.